"On–Off" RGD Signaling Using Azobenzene Photoswitch‐Modified Surfaces1. Issue 10 (1st July 2015) - Vaselli, Elisa; Fedele, Chiara; Cavalli, Silvia; Netti, Paolo A.
Abstract Photoresponsive surfaces were developed by modifying glass slides with switchable Gly‐Arg‐Gly‐Asp‐Ser (GRGDS) peptides to investigate light‐controlled cell adhesion. The GRGDS peptide sequence was attached to an azobenzene moiety and then "clicked" to silanized glass substrates. The photoresponsive behavior of such cell‐instructive materials (CIMs) was first checked by contact angle technique and by recording local changes in wettability owing to the isomerization of the azobenzene domain upon light stimulus. "On–off" switching was observed for at least five cycles when illuminated consecutively with UV and visible‐light sources. Finally, cell‐adhesion studies with human umbilical vein endothelial cells (HUVECs) validated our system as an effective light‐responsive CIM platform and the possibility of dynamically controlled cell adhesion in situ was envisioned.